Latar belakang sejarah dan kultural korupsi di Indonesia - Soedarso, Boesono, 1931- (Jakarta : Penerbit Universitas Indonesia, 2009)
Historical and cultural background of corrupt practices in Indonesia.
Includes bibliographical references (p. 184-185).
Keywords: Political corruption -- Indonesia